Worse associative memory recall in healthy older adults compared to young ones, a face-name study in Spain and Mexico. Issue 6 (3rd July 2021) - Flores Vazquez, Juan Francisco; Rubiño, José; Contreras López, José Juan; Siquier, Antonia; Cruz Contreras, Cecilia; Sosa-Ortiz, Ana Luisa; Enriquez Geppert, Stefanie; Andrés, Pilar
ABSTRACT: Introduction: The Face Name Associative Memory Exam (FNAME) is sensitive to associative memory changes early in the Alzheimer's disease spectrum, but little is known about how healthy aging affects FNAME performance. We aimed to assess aging effects on an extended version of the test, which captures further associative memory abilities beyond the recall and recognition domains measured in the original version. Method: We adapted FNAME versions in Spain and Mexico, adding new subtests (Spontaneous Name Recall, Face-Name Matching). We compared the performance of 21 young adults (YA) and 27 older adults (OA) in Spain, and 34 YA and 36 OA in Mexico. Recall was analyzed using a mixed-model ANOVA including subtest scores as dependent variables, age group as a fixed-factor independent variable, and recall subtest as a three-level repeated-measure independent variable. The rest of the associative memory domains were analyzed through t-tests comparing the performance of YA and OA. Results: In Spain, we found significant effects for age group and recall subtest, with large effect sizes. The recognition subtests (Face Recognition, Name Recognition) displayed ceiling effects in both groups. The new subtests displayed medium-to-large effect sizes when comparing age groups. In Mexico, these results were replicated, additionally controlling for education. In both studies, recall performance improved after repeated exposures and it was sustained after 30 minutes in YA and OA. Conclusions: We document, in two different countries, a clear aging pattern on the extended FNAME: regardless of education, OA remember fewer stimuli than YA through recall subtests. The new subtests provide evidence on associative memory changes in aging beyond recall.